A Basic Study on Production Performance of Local Cows under a Typical Village Condition of Mymensingh District - Hossain, MA; Hashem, MA; Khan, MAS (Journal of Environmental Science and Natural Resources, 2017)
The present piece of research work was conducted to find out the present condition of native cattle rearing, milk production and reproductive parameters and to give important suggestion for production constraints. The experiment was conducted at a nearby village named Boira adjacent to Bangladesh Agricultural University, Mymensingh having eighty three local cows and seventeen heifers were taken under this study from 72 farmers selected with direct interview. Data was compiled statistically only for tabular, percentage, mean and standard deviation. Body weight and condition score of the observed value were 173.23 ± 32.03 kg and 2.55 ±0.34, respectively. Average daily intake of feed was 12.5 kg (fresh basis) and 7.72 kg (DM basis). From the results of experiment, it was found that average daily milk yield of the indigenous cows for whole lactation period was 1.43 ± 0.58 kg. The mean value of hemoglobin, packed cell volume and fat percentage was 7.8±1.00 (g 100 ml-1), 52± 52.10 (%) and 57.6±9.1g/kg, respectively. Age at first calving for local cows found 52.8 ± 13.32 months and calving interval was 417.6±109.5 days. Birth weight of the local calves found 14.43±2.56 kg. Average number of eggs of parasite was 53 per gram of feces. From the study it can be concluded that morphometrics, production and reproduction traits of indigenous cows was favorable and profitable practice in selected areas. J. Environ. Sci. & Natural Resources, 9(2): 115-120 2016